Clean production of isopropyl myristate: A cutting-edge enzymatic approach with a holistic techno-economic evaluation - Shaaban Sadek, M.; Mustafa, Ahmad; Mostafa, N.A.; Di Bitonto, Luigi; Mustafa, Muhamad; Pastore, Carlo (Sustainable Energy Technologies and Assessments, 2024)
International audience This work aims to develop a simple, clean, and energy-efficient lipase-catalyzed method for the synthesis of isopropyl myristate (IPM). The enzymatic esterification between isopropyl alcohol and myristic acid was catalyzed using immobilized Candida Antarctica lipase. Response Surface Methodology (RSM) was applied to study the interactive effect of reaction conditions on IPM yield. The maximum experimental and predicted conversions were 92.4 % and 92.0 %, respectively. The optimized conditions were as follows: molar ratio of isopropyl alcohol to myristic acid molar ratio of 8:1, molecular sieves of 12.5 % w/w, a catalyst load of 4 % w/w, at a temperature of 60 ◦C and a reaction time of 2.5 h. Isopropyl myristate synthesized was isolated and fully characterized by GC–MS, FTIR, 1H and 13C NMR. Finally, to support the applicability perspective of this proposed method, a process diagram (PSD) was created using ASPEN PLUS software to simulate the production of IPM under the optimized conditions. The economic assessment of the whole process produced a positive net present value (NPV) of $44,797,732, return on investment (ROI) of 716.17 %, internal rate of return (IRR) of 110 %, payback period of 1.61, and a levelized cost of production (LCOP) of $1,777 per ton over a 14-year project lifespan. These results strongly suggest low-risk and high-profitability benefits to investing in this green route. Finally, the environmental impact was also assessed by calculating the quantity of CO2 generated from the proposed enzymatic process. The results showed a reduced emission rate of 0.25 ton CO2 eq. per ton of IPM produced. This underscores the lower environmental impact of this technology compared to traditional methods. Importantly, this study stands out as the first to conduct a comprehensive techno-economic assessment of the enzymatic synthesis of IPM, providing valuable insights into the economic viability and potential benefits of adopting this innovative and sustainable approach in the chemical ...